Synthesis of high-ordered mesoporous aluminosilica monoliths using triblock copolymer and application in the water purification - Nasser Zouli (Ain Shams Engineering Journal, 2024)
Mesoporous aluminosilica particulates (MASP) offer a high surface area and specific structural properties that make them effective for adsorbing specific contaminants from drinking water. The MASP’s surface characteristics were studied by SEM, TEM, Mapping-EDX, and BET analysis. Through the use of a batch adsorption approach, this work sought to examine the adsorption behavior of MASP sorbent towards Cd(II) ions at different pH values, time intervals, sorbent doses, and temperatures. MASP’s maximal capacity for Cd(II) ions uptake was 16.5 mg/g at pH 6.5, 25 °C, 0.1 g dose, and 5 h of sorption time. The pseudo-first-order model provided a good description of the uptake process. The best-fitting isotherm was found to be the Langmuir and Redlich–Peterson isotherm. The method came out to be exothermic and spontaneous by thermodynamic analysis. MASP demonstrates durability and reusability during over ten regeneration cycles.